Animal genetic resources management and property rights - CGIAR Program on Collective Action and Property Rights (International Food Policy Research Institute, 2010)
Approximately 2 billion people depend on livestock for at least part, and in some cases most, of their livelihood. The poorest livestock keepers are the ones that most need animals that are tolerant of high temperatures and resistant to diseases and drought. These genetic characteristics are referred to as animal genetic resources (AnGR).